Characterization of mixed methods research in nursing published in the Journal of Mixed Methods Research - José Luís Guedes dos Santos; Greici Capellari Fabrizzio; Caroline Cechinel Peiter; Daiana De Mattia; Daniele Perin; Elisiane Lorenzini (Universidade Federal de Santa Maria, 2020)
Objective: to characterize the scientific production in the field of nursing published in the Journal of Mixed Methods Research. Method: documentary study, with a quantitative approach. Data collection was carried out from April to May 2019, using the term Nursing in the search field of the journal's online page, considering the time frame from 2007 to 2018. The data were analyzed using descriptive statistics. Results: 37 original articles were identified, published mainly since 2011 (70.2%), with emphasis on the United States (45.9%). Concomitant or parallel-convergent triangulation was the main methodological design adopted by the articles (32.4%). In the qualitative and quantitative stages of research, exploratory-descriptive (12.4%) and cross-sectional (21.7%) studies predominated, respectively. Final considerations: there were multiple possibilities in the use of mixed methods in nursing research. The results of the study may help researchers interested in the use of mixed research methods.